The role of cholesterol and mitochondrial bioenergetics in activation of the inflammasome in IBD - Astorga, Jessica; Gasaly, Naschla; Dubois-Camacho, Karen; De la Fuente, Marjorie; Landskron, Glauben; Faber, Klaas Nico; Urra, Félix A.; Hermoso, Marcela A. (Frontiers in Immunology, 2022)
Inflammatory Bowel Disease (IBD) is characterized by a loss of intestinal barrier function caused by an aberrant interaction between the immune response and the gut microbiota. In IBD, imbalance in cholesterol homeostasis and mitochondrial bioenergetics have been identified as essential events for activating the inflammasome-mediated response. Mitochondrial alterations, such as reduced respiratory complex activities and reduced production of tricarboxylic acid (TCA) cycle intermediates (e.g., citric acid, fumarate, isocitric acid, malate, pyruvate, and succinate) have been described in in vitro and clinical studies. Under inflammatory conditions, mitochondrial architecture in intestinal epithelial cells is dysmorphic, with cristae destruction and high dynamin-related protein 1 (DRP1)-dependent fission. Likewise, these alterations in mitochondrial morphology and bioenergetics promote metabolic shifts towards glycolysis and down-regulation of antioxidant Nuclear erythroid 2-related factor 2 (Nrf2)/Peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC-1α) signaling. Although the mechanisms underlying the mitochondrial dysfunction during mucosal inflammation are not fully understood at present, metabolic intermediates and cholesterol may act as signals activating the NLRP3 inflammasome in IBD. Notably, dietary phytochemicals exhibit protective effects against cholesterol imbalance and mitochondrial function alterations to maintain gastrointestinal mucosal renewal in vitro and in vivo conditions. Here, we discuss the role of cholesterol and mitochondrial metabolism in IBD, highlighting the therapeutic potential of dietary phytochemicals, restoring intestinal metabolism and function.